A review of the late Cenozoic genus Bohra (Diprotodontia: Macropodidae) and the evolution of tree-kangaroos - Prideaux, Gavin J.; Warburton, Natalie M. (Zootaxa, 2023)
Tree-kangaroos of the genus Dendrolagus occupy forest habitats of New Guinea and extreme northeastern Australia, but their evolutionary history is poorly known. Descriptions in the 2000s of near-complete Pleistocene skeletons belonging to larger-bodied species in the now-extinct genus Bohra broadened our understanding of morphological variation in the group and have since helped us to identify unassigned fossils in museum collections, as well as to reassign species previously placed in other genera. Here we describe these fossils and analyse tree-kangaroo systematics via comparative osteology. Including B. planei sp. nov., B. bandharr comb. nov. and B. bila comb. nov., we recognise the existence of at least seven late Cenozoic species of Bohra, with a maximum of three in any one assemblage. All tree-kangaroos (Dendrolagina subtribe nov.) exhibit skeletal adaptations reflective of greater joint flexibility and manoeuvrability, particularly in the hindlimb, compared with other macropodids. The Pliocene species of Bohra retained the stepped calcaneocuboid articulation characteristic of ground-dwelling macropodids, but this became smoothed to allow greater hindfoot rotation in the later species of Bohra and in Dendrolagus. Tree-kangaroo diversification may have been tied to the expansion of forest habitats in the early Pliocene. Following the onset of late Pliocene aridity, some tree-kangaroo species took advantage of the consequent spread of more open habitats, becoming among the largest late Cenozoic tree-dwellers on the continent. Arboreal Old World primates and late Quaternary lemurs may be the closest ecological analogues to the species of Bohra.